Research progress on polythiophene and its application as chemical sensor - Abdullah, ‪Norli; Norizan, Mohd Nurazzi; Moklis, Muhammad Harussani; Ngah Demon, Siti Zulaikha; Abdul Halim, Norhana; Mohamad, Imran Syakir; Bahruji, Hasliza (Penerbit UPNM, 2022)
The π-conjugated polymers and their derivatives have attracted significant attention in recent decades for research and development as chemical sensor. This is because of their wide range of potential applications especially as an active layer in various electronic devices. The organic structure of these polymers had confer the electronic and material properties and facilitate their processibility. This includes several promising of conjugated polymers such as polyacetylene, polyaniline, polypyrole, polythiophene (PTh) and etc. Above all, the conjugated polythiophene and its derivatives stand out as one of the promising members of the conjugated polymer family. Due to their unique in electrical characteristics, excellent environmental and thermal stability, low-cost synthesis, and mechanical strength, various procedures have been invoked in order to increase the usability of polythiophene. This includes side chain functionalization of the different derivatives and copolymers, functionalised with carbonaceous materials, and combination of both of these strategies. In this review, focus is on the present conductive polymers, the characteristics and the synthesization of polythiophene and its derivatives, and their applications in chemical sensor are highlighted at the last part.